Global, regional, and national caries of permanent teeth incidence, prevalence, and disability-adjusted life years, 1990-2021: analysis for the global burden of disease study - Zhiyuan Li; Chenhang Yu; Huan Chen (BMC Oral Health)
Abstract Objectives This study aims to analyze the global, regional, and national incidence, prevalence, and disability-adjusted life years (DALYs) related to caries of permanent teeth from 1990 to 2021, as part of the Global Burden of Disease Study (GBD). Study design and methods Data on incidence, prevalence, and DALYs were extracted and analyzed for various demographic and regional categories. Age-standardized incidence rates (ASIR), age-standardized prevalence rates (ASPR), and age-standardized DALY rates (ASDAR) were calculated. Temporal trends and associations with sociodemographic index (SDI) were also examined. Results In 2021, there were approximately 2.37 billion cases of caries of permanent teeth, with an ASIR of 29,777.03 per 100,000 population. The prevalence was around 2.24 billion, with an ASPR of 27,543.34 per 100,000. Females exhibited a higher disease burden than males, and the burden increased with age, peaking in the 20–24 age group. Regions with lower SDI showed higher ASIRs, while the highest burden was noted in Tropical Latin America. Significant increases in disease burden were observed from 1990 to 2021, particularly in China and Colombia, while Japan showed a decrease. The Bayesian age-period-cohort (BAPC) predictions indicate that the burden of caries of permanent teeth will continue to increase year by year. Conclusion The burden of caries of permanent teeth varies significantly across regions and demographics, with higher rates in lower SDI areas. The findings underscore the importance of targeted interventions and resource allocation in high-burden regions to improve dental health outcomes.